Live imaging of the Drosophila ovarian germline stem cell niche - Wilcockson, Scott G. (STAR Protoc, 2021)
The maintenance of stem cell populations and the differentiation of their progeny is coordinated by specific communication with associated niche cells. Here, we describe a protocol for short-term live imaging of the Drosophila ovarian germline stem cell niche ex vivo. By immobilizing the ovarian tissue in a fibrinogen-thrombin clot, we are able to maintain the tissue for short-term high-temporal live imaging. This enables the visualization of dynamic cellular processes, such as the cytoskeletal dynamics that control stem cell niche communication. For complete details on the use and execution of this protocol, please refer to Wilcockson and Ashe (2019).